First results on the Aterian of Bizmoune Cave (Essaouira, Morocco) - (:unkn) unknown (My University, 2018)
Bizmoune cave is located in southwestern Morocco on the south-facing slopes of JebelHadid, about 15 km northeast of the modern city of Essaouira. The cave was first identifiedas a Paleolithic site in 2008. The current project, a collaboration between Moroccan, French,German and American researchers and institutions, began in 2014. Archaeological deposits atthe site span the Neolithic, Upper Paleolithic/LSA (Ibero-Maurusian) and MSA (Aterian):the majority of the stratigraphic sequence contains Aterian assemblages. Bizmoune caveholds the potential to provide much unique information about Aterian adaptations in alittle-explored area of western North Africa. Current chronometric information places theAterian deposts in MIS 4 and 5, but it is likely that the earliest archaeological depositspredate the last Interglacial. Aterian layers document changing occupational intensity, withsparse remains at the top of the sequence and deposits very rich in organics and archaeologicalmaterials in the lower part of the sequence. Typical Aterian shaped tools such as tangedpieces and bifacial foliates are relatively abundant, and shell beads have been recoveredfrom the earliest Aterian layers as well. The faunal assemblages, which consist mainly ofAfrican bovids, appear to be primarily or entirely anthropogenic in origin. The presence ofshells of typical marine food species such as Mytilus is noteworthy given the site’s distancefrom the sea during the Pleistocene. The density of land snail shells is very high in theNeolithic, Ibero-Maurusian but also in the earliest MSA deposits. Further study is requiredto determine whether the Aterian snail shells were accumulated by hominins or were theresults of natural deaths within the cave.
Keywords: African Research